A Synthetic DNA‐Binding Domain Guides Distinct Chromatin‐Modifying Small Molecules to Activate an Identical Gene Network1. (11th June 2015) - Han, Le; Pandian, Ganesh N.; Chandran, Anandhakumar; Sato, Shinsuke; Taniguchi, Junichi; Kashiwazaki, Gengo; Sawatani, Yoshito; Hashiya, Kaori; Bando, Toshikazu; Xu, Yufang; Qian, Xuhong; Sugiyama, Hiroshi
Abstract Synthetic dual‐function ligands targeting specific DNA sequences and histone‐modifying enzymes were applied to achieve regulatory control over multi‐gene networks in living cells. Unlike the broad array of targeting small molecules for histone deacetylases (HDACs), few modulators are known for histone acetyltransferases (HATs), which play a central role in transcriptional control. As a novel chemical approach to induce selective HAT‐regulated genes, we conjugated a DNA‐binding domain (DBD) "I" to N‐(4‐chloro‐3‐trifluoromethyl‐phenyl)‐2‐ethoxy‐benzamide (CTB), an artificial HAT activator. In vitro enzyme activity assays and microarray studies were used to demonstrate that distinct functional small molecules could be transformed to have identical bioactivity when conjugated with a targeting DBD. This proof‐of‐concept synthetic strategy validates the switchable functions of HDACs and HATs in gene regulation and provides a molecular basis for developing versatile bioactive ligands.